2016
DOI: 10.1371/journal.pone.0146454
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of a Thermostable and Highly Halotolerant GH5 Cellulase from an Icelandic Hot Spring Isolate

Abstract: With the ultimate goal of identifying robust cellulases for industrial biocatalytic conversions, we have isolated and characterized a new thermostable and very halotolerant GH5 cellulase. This new enzyme, termed CelDZ1, was identified by bioinformatic analysis from the genome of a polysaccharide-enrichment culture isolate, initiated from material collected from an Icelandic hot spring. Biochemical characterization of CelDZ1 revealed that it is a glycoside hydrolase with optimal activity at 70°C and pH 5.0 that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 64 publications
3
38
0
4
Order By: Relevance
“…Moreover, Cel5R shows activity in the presence of high salt concentration. Recently, it has been reported that the halophilic cellulase isolated from Icelandic hot spring showed decreased activity in the presence of increasing concentration of NaCl compared to control reaction with no salt19. On the other hand, the thermophilic GH5 endoglucanase isolated from Thermoanaerobacter tengcongensis MB4 retains less than 15% of its activity after 12-hours of pre-incubation in 4 M NaCl55.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Cel5R shows activity in the presence of high salt concentration. Recently, it has been reported that the halophilic cellulase isolated from Icelandic hot spring showed decreased activity in the presence of increasing concentration of NaCl compared to control reaction with no salt19. On the other hand, the thermophilic GH5 endoglucanase isolated from Thermoanaerobacter tengcongensis MB4 retains less than 15% of its activity after 12-hours of pre-incubation in 4 M NaCl55.…”
Section: Discussionmentioning
confidence: 99%
“…The Cel5R shows thermostability up to 58 °C and pH stability from 5–9. Surprisingly, the Cel5R shows halotolerance and extreme halostability in 4 M NaCl, 3 M LiCl and 2 M KCl which is higher than other known halostable cellulases1819. Thus, the combination of extreme halostability with moderate thermal and pH stability makes Cel5R a potential candidate for industrial applications.…”
mentioning
confidence: 94%
“…However, there are reports of obtaining a highly thermostable enzyme with activity at low pH values. Zarafeta et al (2016) characterized thermostable (70 °C) and highly halotolerant cellulases derived from a hot spring isolate. Fig.…”
Section: The Characteristics Of the Biopreparationmentioning
confidence: 99%
“…Such organisms are encountered in all types of terrestrial and marine hot environments, and are represented only by bacterial and archaeal species. Hyperthermostable enzymes encoded in such genomes can be identified by screening genomic or metagenomic material, either bioinformatically (Levisson et al, 2007; Graham et al, 2011; Zarafeta et al, 2016) or through functional genomic screening (Ewis et al, 2004; Tirawongsaroj et al, 2008; Peng et al, 2011). …”
Section: Introductionmentioning
confidence: 99%